Market orientation and marketing innovation on competitive advantage on Y.O.U cosmetic brand - Afyka Sakinah; Vidya Rini Dwita (Marketing Management Studies, 2021)
The purpose of this study was to analyze: The effect of market orientation and marketing innovation on competitive advantage in the Y.O.U cosmetic brand in Padang City. The population in this study are consumers who have bought and used Y.O.U cosmetics in Padang. The number of samples in this study were 100 people using nonprobability sampling. The analysis technique used is SPSS. This research is a causative descriptive research. The results of this study indicate that: (1) Market orientation has a positive and significant effect on the competitive advantage of YOU cosmetic products in the city of Padang. (2) Marketing innovation has a positive and significant effect on the competitive advantage of YOU cosmetic products in the city of Padang. (3) Market orientation and marketing innovation together have a positive and significant effect on the competitive advantage of YOU cosmetics in the city of Padang.